2009
DOI: 10.2217/17435889.4.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Therapeutic Nanoparticles

Abstract: A total of six nanotherapeutic formulations are already approved for medical use and more are in the approval pipeline currently. Despite the massive research effort in nanotherapeutic materials, there is relatively little information about the toxicity of these materials or the tools needed to assess this toxicity. Recently, the scientific community has begun to respond to the paucity of information by investing in the field of nanoparticle toxicology. This review is intended to provide an overview of the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 138 publications
1
46
0
Order By: Relevance
“…Thus, it has been concluded that the interaction depends upon how the biological cells respond to foreign materials in general, ie, the basic mechanism of incorporation, degradation, or bioaccumulation causing cell damage and changes in gene expression. 37,38 A very common method of evaluating the effects of different substances in cell cultures is the MTT assay, which is used to measure the mitochondrial function of cells in vitro ( Figure 4A). Herein, glioma cancer stem cells were found to interact strongly with our gold nanoparticle-based drug delivery vectors.…”
Section: Mtt Cytotoxicity Assaymentioning
confidence: 99%
“…Thus, it has been concluded that the interaction depends upon how the biological cells respond to foreign materials in general, ie, the basic mechanism of incorporation, degradation, or bioaccumulation causing cell damage and changes in gene expression. 37,38 A very common method of evaluating the effects of different substances in cell cultures is the MTT assay, which is used to measure the mitochondrial function of cells in vitro ( Figure 4A). Herein, glioma cancer stem cells were found to interact strongly with our gold nanoparticle-based drug delivery vectors.…”
Section: Mtt Cytotoxicity Assaymentioning
confidence: 99%
“…However, systematic studies on the possible adverse effects of the introduction of the NPs in the body are absent (Soenen et al, 2011), and in fact there are many aspects of the problem that should be considered, ranging from the kind of particles and coatings used to the type of cells employed and the assay chosen for toxicity evaluation. Some reviews have been recently elaborated on the subject (De Jong & Borm, 2008;Hussain et al, 2009;Lewinski et al, 2008;Maurer-Jones et al, 2009;Pelley et al, 2009;Singh et al, 2010;Soenen et al, 2011), and so we will give only a brief account, mainly focused on the kind of particles used in our investigation. We will hence not consider the particular case of drug vehicles designed to be delivered to the patient though respiratory ways (Oberdörster, 2009), as in this route the first unwanted effects can occur already in the lung cells, and only later, after passing the alveolo-capillary barrier, they can get into the bloodstream and spread in the body, where either beneficial or undesired effects can occur as well.…”
Section: General Conceptsmentioning
confidence: 99%
“…Generally, nanotoxicity denotes to the nano-objects aptitude to disturb the normal physiological processes and/or to interrupt the normal structure of organs and tissues. Several review reports on a current toxicology of frequently used inorganic nanoparticles (iron oxides, gold, quantum dots nanoparticles) state that the nanoparticles toxicity mainly depends on numerous intrinsic parameters, such as the nanoparticles composition, stability, size and shape, surface charge and the nature of the surface coating as well as on administered dose and host immunological integrity (Maurer-Jones et al, 2009;Soenen et al, 2011a, b;Yildirimer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%